The THE POSITION OF THE TWO IRAQI KURDISH PARTIES (PDK, PUK) ON THE SINJAR AGREEMENT 2020 - Babla, Dalshad (Humanities Journal of University of Zakho, 2024)
On October 10, 2020, the Sinjar agreement was signed to restore stability and normalise the situation between the federal government in Baghdad and the Kurdistan Regional Government-Iraq after a disagreement and conflict between the two parties on how to manage the district in terms of administration and security. Following the deteriorating situation that the Sinjar district has become after its liberation from the terrorist organisation ISIS in 2016, the agreement the territory. This study aims to indicate the official position of both Kurdish parties on the aforementioned agreement. The analysis also assumes that there is a difference in their positions on the deal based on several reasons. However, this agreement dates back to the situation in the district before the occupation of ISIS and the returning of the Kurdish influence to the region. However, the position of the two Kurdish parties was different regarding the agreement. The Kurdish Democratic Party (KDP) was more interested in the agreement and its implementation compared to the Patriotic Union of Kurdistan (PUK), and this comes because the performance of the agreement will restore the influence of the KDP to the district exclusively and will remove the impact of the allies of the PUK from the militias of the Kurdistan Workers Party PKK and the Popular Mobilization Forces PMF from it.